Combined Spectroscopic and TD-DFT Analysis to Elucidate Substituent and Acidochromic Effects in Organic Dyes: A Case Study on Amino- versus Nitro-Substituted 2,4-Diphenylquinolines - dos Santos, Giovanny Carvalho [UNESP]; Roldao, Juan Carlos; Shi, Junqing; Milián-Medina, Begoña; da Silva-Filho, Luiz Carlos [UNESP]; Gierschner, Johannes (Wiley, 2020)
A combined spectroscopic and TD-DFT case study was performed, to identify a robust method to calculate the complex near UV/Vis absorption spectra of various amino- vs. nitro-substituted 2,4-diphenylquinolines, which vary strongly under neutral and successively acidic conditions. For this, different DFT functionals were tested for geometry optimization and the TD part to calculate the neutral and different protonated species in a fast screening approach, i. e. using single point calculations in an implicit solvent. Offset-corrected M06HF, hitherto only applied to polymers, was identified as a suitable method to reproduce the absorption spectra in a reasonable fashion for all different substitution pattern and all different protonated species at different pH values; moreover, the method properly predicts the energetic ordering of low-lying n-π* and ππ* transitions, which is decisive for the non-/emissive nature of the different compounds. In all, this might provide a valuable tool for computer-aided design of related classes of compounds.
Keywords: absorption spectra; acidochromism; density functional theory; dual emission; fluorescence; quinolines